PENGARUH PERSAINGAN, SISTEM PENJUALAN DAN SELERA KONSUMEN TERHADAP VOLUME PENJUALAN SEPEDA MOTOR MEREK YAMAHA ALL NEW NMAX 155 VVA PADA PT THAMRIN BROTHERS DI KOTA BATURAJA - Hema Malini; Rini Apriyani; Henny Sjafitri; Rahmat Hidayatullah (STIE DWI SAKTI BATURAJA, 2022)
The purpose of this study was to determine the effect of competition, sales system and consumer tastes to sales volume of Yamaha ALL NEW NMAX 155 VVA brand motorcycle at PT Thamrin Brothers in Baturaja city. This research is a descriptive study and using accidental sampling with a sample size of 87 respondents. Using multiple regression analysis techniques and to test the research hypothesis used, the F-test and t test. From the calculation results, it is found that; 1) The coefficient value of Competition (X1) is (0,686), 2) The coefficient of Sales System (X2) is (0,203), 3) The coefficient of Consumer Tastes (X3) is (0,084), this means Competition, Sales System and Consumer Tastes affect the Sales Volume by customers. From the results of the t test hypothesis, the following results are obtained; 1) The value of t count of Competition (X1) (7,712) > t tabel (1,988) means that there is an influence of Competition on Sales Volume, 2) The value of t count of Sales System (X2) is (2,274) > t tabel (1,988) means that there is an the effect of Sales System on Sales Volume, 3) The value of t count of Consumer Tastes (X3) is (0,788) < t table (1,988) which means that there is no effect of Consumer Tastes of Sales Volume. Meanwhile, from the results of the hypothesis test, it is found that the value of Fcount (356,275) > F table (3,96), this means that the variables of Competition, Sales System and Consumer Tastes together have a significant effect on sales volume of Yamaha ALL NEW NMAX 155 VVA brand motorcycle at PT Thamrin Brothers in Baturaja city.